PENGARUH PENDEKATAN PEMBELAJARAN KONTESKTUAL TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI PANJANG DAN BERAT DI KELAS III SEKOLAH DASAR - Rifda Afifah; Destrinelli; Akhmad Faisal Hidayat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the contextual learning approach on the critical thinking skills of third-grade elementary school students on the topic of length and weight. The research employed a quantitative approach using a pre-experimental design, specifically the One-Group Pretest–Posttest Design. The research subjects consisted of all third-grade students of SDN 124/1 Batin, totaling 26 students. The sampling technique used was saturated sampling. Data were collected through pretest and posttest instruments designed to measure students’ critical thinking skills. The obtained data were analyzed using statistical tests with the assistance of SPSS version 21. Prior to hypothesis testing, prerequisite analyses in the form of normality and homogeneity tests were conducted. The results of the normality test indicated that the data were not normally distributed; therefore, hypothesis testing was carried out using the nonparametric Wilcoxon Signed Rank Test. Descriptive analysis results showed an increase in the average score of students’ critical thinking skills from 43.04 in the pretest to 63.73 in the posttest. The results of the Wilcoxon test revealed a significance value of 0.000 (< 0.05), indicating a significant difference in students’ critical thinking skills before and after the implementation of the contextual learning approach. Thus, it can be concluded that the contextual learning approach has a significant effect on improving the critical thinking skills of third-grade elementary school students on the topic of length and weight